THE TAXONOMIC TREAMENT OF CAMELLIA LUUANA (SECT. DALATIA) IN THE CENTRAL HIGHLANDS, VIETNAM - Le, Nguyet Hai Ninh (Trường Đại học Đà Lạt, 2023)
Camellia luuana Orel & Curry is known only from its type locality, Ta Dung Nature Reserve, now Ta Dung National Park, Dak Nong Province, the Central Highlands of Vietnam. No characteristics of fruit and seeds, which are the most important to divide genera in Theaceae (Chang & Ren, 1998; Ming & Bartholomew, 2007; Sealy, 1958), were presented in its protologue. After carefully reviewing the protologue, specimens, and images of Camellia luuana, relevant species and genera, and conducting a field investigation around its type locality, we concluded that this species is not a member of Camellia, but a member of  Pyrenaria.